Is the Cone Penetration Test (CPT) Useful for Arctic Site Investigation? - McCallum, A B; Barwise, Andy; Santos, Roi S (Volume 10: Polar and Arctic Science and Technology, 2014)
A warming Arctic provides increased opportunity for infrastructure development. Although the cone penetration test is used globally for site investigation in unfrozen soils, this discussion paper investigates the use of cone penetration testing to provide in situ data in frozen geomaterials. Historical and contemporary use of cone penetration testing in permafrost, snow, terrestrial ice and sea ice is reviewed, and work conducted across alpine, Arctic and Antarctic environs is considered. Although frozen geomaterials offer challenges to any in situ media assessment, with suitable equipment, cone penetration testing in frozen geomaterials typical of the Arctic is possible.